Aspectos bionomicos da betara Menticirrhus americanus (Linnaeus, 1758) na baia de Ubatuba-Enseada, São Francisco do Sul - SC, Brasil - Haluch, Carolina Ferreira (2008)
Orientador : Prof. Dr. Marco Fabio Maia Correa